Albumin-Globulin Ratio and Common Carotid Artery Intima-Media Thickness in Patients with Ischemic Stroke - Han, Qiao; You, Shoujiang; Miao, Mengyuan; Zheng, Danni; Du, Huaping; Sun, Yaming; Zhai, Wanqing; Zhong, Chongke; Cao, Yongjun; Liu, Chun-Feng (Current neurovascular research, 2025)
The relationships between serum albumin, albumin-globulin (A/G) ratio, globulin and atherosclerosis in acute ischemic stroke (AIS) remain uncertain. We investigated the associations between serum albumin, A/G ratio, globulin levels and carotid atherosclerosis in patients with AIS. A total of 1,339 AIS patients were enrolled. Admission A/G ratio was divided into quartiles, and serum albumin and globulin levels were also categorized. Carotid atherosclerosis was detected through the assessment of common carotid artery intima-media thickness (cIMT), and abnormal cIMT was characterized by mean and maximum cIMT values of ≥1 mm. We evaluated the relationships between A/G ratio, albumin, globulin and abnormal cIMT, using multivariable logistic regression models. In the multivariable-adjusted analysis, the highest A/G ratio quartile (Q4) was linked to a 59% decreased risk of abnormal mean cIMT (OR 0.41; 95% CI 0.29-0.60) and a 58% decreased risk of abnormal maximum cIMT (OR 0.42; 95% CI 0.30-0.60) when compared to the lowest quartile (Q1), respectively. Moreover, decreased albumin and elevated globulin levels were also associated with abnormal mean cIMT and maximum cIMT. In addition, the A/G ratio provided supplementary predictive capability beyond the already established risk factors, and the C-statistic of the A/G ratio for abnormal cIMT is larger than globulin (P <0.01). Decreased serum A/G ratio, albumin and elevated serum globulin were independently associated with abnormal cIMT in AIS patients. Moreover, the A/G ratio appeared to be a better predictor of abnormal cIMT.